STUDENT AND CULTURE: STORY OF BANYUWANGI - Muttafaqur Rohmah (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2019)
Culture in the eyes of students different with adult thinking. They blinded by new cultures that suddenly appear on the surface, breaking the line of thought, releasing one by one the indigenous veins and regions that have actually become one in their souls. When they have to talk about culture, they look for things from Google, don't ask grandfather, or people who understand and are elder in their villages, because Google has a more interesting answer than they would ask the œancestors". This paper is interesting in the description of the results of student writing that tells folklore developing in the area, the results of stories written by students consisting of a collection of folklore divided into three volumes, Keras Cinta Jogopati, Mas Age and Mas Alit, and Darah Merah Sidopekso. The three collections of stories were written by students of SMAN 1 Banyuwangi within a period of one semester sourced from basic competencies 3.7 namely the assessment of values and content contained in folklore (saga) both oral and written ˜mengidentifikasi nilai-nilai dan isi yang terkandung dalam cerita rakyat (hikayat) baik lisan maupun tulis.